2011
DOI: 10.1186/1741-7007-9-54
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and characterization of a set of conserved and new regulators of cytoskeletal organization, cell morphology and migration

Abstract: BackgroundCell migration is essential during development and in human disease progression including cancer. Most cell migration studies concentrate on known or predicted components of migration pathways.ResultsHere we use data from a genome-wide RNAi morphology screen in Drosophila melanogaster cells together with bioinformatics to identify 26 new regulators of morphology and cytoskeletal organization in human cells. These include genes previously implicated in a wide range of functions, from mental retardatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
172
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(185 citation statements)
references
References 48 publications
9
172
3
1
Order By: Relevance
“…4 It is conceivable that perturbations in ciliogenesis or basal body function, processes that are interconnected with microtubule growth dynamics, may account for the peculiar effects on ␤-catenin/Wnt readouts in HectD1-and Trabid-depleted cells (51,52). 4 The enzymatic activities of HectD1 and Trabid might be regulated by signals that inhibit or promote cell migration, which would be consistent with the proposed roles of these enzymes as regulators of cell motility (25,34). Interestingly, HectD1 and Trabid are putative novel components of the STRI-PAK complex (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…4 It is conceivable that perturbations in ciliogenesis or basal body function, processes that are interconnected with microtubule growth dynamics, may account for the peculiar effects on ␤-catenin/Wnt readouts in HectD1-and Trabid-depleted cells (51,52). 4 The enzymatic activities of HectD1 and Trabid might be regulated by signals that inhibit or promote cell migration, which would be consistent with the proposed roles of these enzymes as regulators of cell motility (25,34). Interestingly, HectD1 and Trabid are putative novel components of the STRI-PAK complex (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…1B). These Trabid-interacting proteins are known components of the STRIPAK (Striatin-interacting phosphatase and kinase) complex and include the Striatin family of WD40 domain proteins that function as regulatory subunits of protein phosphatase PP2A; factors that regulate cortical actin cytoskeleton dynamics: cortactin-binding protein 2, CTTNBP2NL, and FAM40A; and the centrosome-associated protein SLMAP (32)(33)(34). Interestingly, we did not find any PP2A subunits in the Trabid IPs, suggesting mutually exclusive or transient association of subcomplexes of STRIPAK to Trabid and PP2A (33).…”
Section: Identification Of E3 Ubiquitin Ligase Hectd1 In a Trabidmentioning
confidence: 99%
“…Striatins are highly enriched at dendritic spines (Gaillard et al, 2006), and the Mob protein family has been shown to regulate synapse formation in Drosophila (Schulte et al, 2010). FAM40A and FAM40B have recently been shown to modulate the actin cytoskeleton (Bai et al, 2011). It is unclear whether CTTNBP2 also associates with the PP2A complex in neurons; if so, the PP2A complex likely dephosphorylates the cortactin-CTTNBP2 complex and regulates F-actin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to rac1 and mbc, two other suppressors that were identified in the deficiency screen, rhoA and wasp, also play important roles in cytoskeleton regulation, and a mutation of rac2 also suppressed ( Figure 5L and Table 2). In addition, we identified the suppressor locus CG32138 that encodes a homolog of the human formin genes that have been implicated in actin cytoskeleton regulation (Table 1) (Bai et al 2011). We assessed the effect of en .…”
Section: Rac Rho and The Cytoskeletonmentioning
confidence: 99%